2019
DOI: 10.1136/thoraxjnl-2018-212877
|View full text |Cite
|
Sign up to set email alerts
|

Ambient air pollution exposure and risk and progression of interstitial lung abnormalities: the Framingham Heart Study

Abstract: BackgroundAmbient air pollution accelerates lung function decline among adults, however, there are limited data about its role in the development and progression of early stages of interstitial lung disease.AimsTo evaluate associations of long-term exposure to traffic and ambient pollutants with odds of interstitial lung abnormalities (ILA) and progression of ILA on repeated imaging.MethodsWe ascertained ILA on chest CT obtained from 2618 Framingham participants from 2008 to 2011. Among 1846 participants who a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 48 publications
0
40
0
2
Order By: Relevance
“… 27 , 28 The total annual R 2 for EC estimates was 0.71–0.75 for 2004–2008. 29 Twenty-four hour estimates of ground-level ozone (O 3 ) exposure (at a 1 × 1 km resolution) was assigned using a prediction model, which also used a hybrid neural network using GEOS-Chem transport simulations, land use terms, and satellite-based estimates of total column and vertical profile O 3 (to estimate the fraction of ground-level O 3 in the total column O 3 ). 30 Finally, to account for tropospheric reactions of precursors that produce and deplete O 3 , the neural network model included emissions inventory daily United States Environmental Protection Agency (USEPA) Air Quality System measures of sulfur dioxide, nitrogen dioxide, nitrogen oxides, and volatile organic compounds.…”
Section: Methodsmentioning
confidence: 99%
“… 27 , 28 The total annual R 2 for EC estimates was 0.71–0.75 for 2004–2008. 29 Twenty-four hour estimates of ground-level ozone (O 3 ) exposure (at a 1 × 1 km resolution) was assigned using a prediction model, which also used a hybrid neural network using GEOS-Chem transport simulations, land use terms, and satellite-based estimates of total column and vertical profile O 3 (to estimate the fraction of ground-level O 3 in the total column O 3 ). 30 Finally, to account for tropospheric reactions of precursors that produce and deplete O 3 , the neural network model included emissions inventory daily United States Environmental Protection Agency (USEPA) Air Quality System measures of sulfur dioxide, nitrogen dioxide, nitrogen oxides, and volatile organic compounds.…”
Section: Methodsmentioning
confidence: 99%
“…Interstitial lung abnormalities (ILA) are defined as specific patterns of increased lung densities identified on high-resolution computed tomography (HRCT) scans, usually in subjects without previous diagnosis of pulmonary disease. ILA are frequently observed with advanced age and are associated with smoking history and environmental pollution [1][2][3]. However, ILA are also observed in non-smokers and in some studies the development of these abnormalities was not dependent on smoking status at baseline [4].…”
Section: Introductionmentioning
confidence: 96%
“…20 Rice et al conducted a community-dwelling population-based study in Framingham and reported that higher long-term exposure to elemental carbon, an indicator of traffic pollution, was associated with the incidence and progression of interstitial lung abnormalities (ILAs); however, they found no association between average levels of PM2.5 and incident ILAs. 12 In detail, unlike the positive association found between elemental carbon (OR 1.27, 95% CI 1.04 to 1.55) as well as PM2. Atherosclerosis (MESA) Lung study and reported that exposure to ambient NO X was associated with a higher prevalence of ILAs, but the association was not found with exposure to PM2.5 and O 3 .…”
Section: Open Accessmentioning
confidence: 85%